High‐resolution electrical mapping of porcine gastric slow‐wave propagation from the mucosal surface. Issue 5 (29th December 2016) - Angeli, T. R.; Du, P.; Paskaranandavadivel, N.; Sathar, S.; Hall, A.; Asirvatham, S. J.; Farrugia, G.; Windsor, J. A.; Cheng, L. K.; O'Grady, G.
Abstract: Background: Gastric motility is coordinated by bioelectrical slow waves, and gastric dysrhythmias are reported in motility disorders. High‐resolution (HR) mapping has advanced the accurate assessment of gastric dysrhythmias, offering promise as a diagnostic technique. However, HR mapping has been restricted to invasive surgical serosal access. This study investigates the feasibility of HR mapping from the gastric mucosal surface. Methods: Experiments were conducted in vivo in 14 weaner pigs. Reference serosal recordings were performed with flexible‐printed‐circuit (FPC) arrays (128‐192 electrodes). Mucosal recordings were performed by two methods: (i) FPC array aligned directly opposite the serosal array, and (ii) cardiac mapping catheter modified for gastric mucosal recordings. Slow‐wave propagation and morphology characteristics were quantified and compared between simultaneous serosal and mucosal recordings. Key Results: Slow‐wave activity was consistently recorded from the mucosal surface from both electrode arrays. Mucosally recorded slow‐wave propagation was consistent with reference serosal activation pattern, frequency ( P ≥.3), and velocity ( P ≥.4). However, mucosally recorded slow‐wave morphology exhibited reduced amplitude (65‐72% reduced, P <.001) and wider downstroke width (18‐31% wider, P ≤.02), compared to serosal data. Dysrhythmias were successfully mapped and classified from the mucosal surface, accorded with serosal data, and were consistent with known dysrhythmic mechanisms in the porcine model. Conclusions & Inferences: High‐resolution gastric electrical mapping was achieved from the mucosal surface, and demonstrated consistent propagation characteristics with serosal data. However, mucosal signal morphology was attenuated, demonstrating necessity for optimized electrode designs and analytical algorithms. This study demonstrates feasibility of endoscopic HR mapping, providing a foundation for advancement of minimally invasive spatiotemporal gastric mapping as a clinical and scientific tool. Abstract : High‐resolution electrical mapping has advanced the accurate assessment of gastric dysrhythmias, offering promise as a diagnostic technique, but has been restricted to invasive surgical access to date. This study investigated high‐resolution electrical mapping from the gastric mucosal surface as feasibility for endoscopic gastric electrical mapping. Slow‐wave activity was consistently recorded from the mucosal surface, and propagation was consistent with reference serosal activation pattern, frequency, and velocity, including during dysrhythmias; however, mucosal waveforms exhibited reduced amplitude and wider downstroke width. This study demonstrates feasibility of endoscopic high‐resolution mapping, providing a foundation for advancement of minimally invasive spatiotemporal gastric mapping as a clinical and scientific tool.